Inhalation injury after a landmine explosion: a case report - Woojung Kim; Donghoon Kim; Sung Yub Jeong; Yoonhyun Lee; Hojun Lee (Journal of Trauma and Injury)
Blast injuries are divided into four classes, and inhalation injuries are a quaternary class of blast injuries. An inhalation injury can be critical to the patient due to the possibility of related complications, such as airway obstruction resulting from upper airway edema and pneumonia. Once diagnosed, an inhalation injury should be treated with early intubation, aerosol therapy, and antibiotics as soon as possible. We should suspect this injury in circumstances involving fire and especially bomb attacks in a military setting. Antipersonnel landmines designed to damage the soldier by amputating the leg can cause blast injuries, but their power is limited to the lower extremity. However, we found an inhalation injury in a victim whose leg had been amputated by an antipersonnel landmine. As soon as we suspected an inhalation injury, we intubated the patient to preserve his airway and started acetylcysteine/heparin aerosol therapy. The patient also was treated with proper antibiotics for right lower lung pneumonia that developed as a sequela of inhalation injury. We could extubate the patient without any complications such as airway obstruction on the third day of intensive care, after which the patient was transferred to the general ward for active rehabilitation. This report presents the first known case of inhalation injury due to a landmine explosion.